The optimal design of deep foundation pit dewatering under the influence of waterproof curtain - Li, Xiaofeng; Wang, Binghua; Xu, Jianhang; Zhang, Xianmeng (Archives of Civil Engineering, 2026)
Improper disposal of foundation pit dewatering can cause engineering problems such as uneven settlement, slope instability, quicksand, piping, etc., and pose a huge threat to construction safety. Therefore, it is necessary to optimize the design of foundation pit dewatering engineering. This paper introduces a simulation-optimization model for this problem, establishes a groundwater flow simulation model using MODFLOW-2005 as a platform, and uses LGR local grid densification technology to densify the dewatering area of foundation pits with different curtain depths. Under the premise of ensuring construction safety, the minimum cost is the objective function, and GWM-2005 is used to solve the optimization model of the foundation pit engineering example. The results show that with the increase of the curtain depth, the optimal design can effectively reduce the number of pumping wells and the total amount of pumping water in the foundation pit dewatering project, reasonably optimize the layout of the pumping well position, significantly improve the safety of foundation pit construction, effectively reduce the impact of foundation pit dewatering project on the surrounding geological environment, and effectively control the land subsidence problem in the precipitation process.
Keywords: foundation pit dewatering; curtain depth; simulation-optimization model; response matrix method; GWM-2005